2023
DOI: 10.3390/su151310713
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Effects of DEE Pilot Injection on a Biogas-Fueled HCCI Engine at Different Injection Locations

Abstract: One of the popular ways to minimise the impact of emissions produced by engines is by enabling alternative fuels. Out of the many trending options for alternative fuels, biogas provides some unique advantages, such as being considered to be environmentally friendly, obeying the laws of renewable energy and generating the smallest carbon footprints. The two major drawbacks of traditional diesel engines are their high rate of NOx and significant amount of soot. The best candidates for overcoming these issues are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…The possibility of enhancing the combustion characteristics of methane by blending it with hydrogen has been investigated as well by Yap et al and the results highlighted a reduction of the intake temperature needed to have combustion and lower NOx emissions [9]. An investigation on the effects of diethyl-ether (DEE) pilot injection on a biogas-fuelled HCCI engine at different injection locations has been performed by Mishra et al with DEE acting as an ignition source and results showed that port injection provides higher thermal efficiency than manifold injections, while lower emissions were observed in manifold injections [10]. Feroskhan et al studied the operation of a Homogeneous Charge Compression Ignition (HCCI) engine using simulated biogas and DEE as the primary and secondary fuels respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of enhancing the combustion characteristics of methane by blending it with hydrogen has been investigated as well by Yap et al and the results highlighted a reduction of the intake temperature needed to have combustion and lower NOx emissions [9]. An investigation on the effects of diethyl-ether (DEE) pilot injection on a biogas-fuelled HCCI engine at different injection locations has been performed by Mishra et al with DEE acting as an ignition source and results showed that port injection provides higher thermal efficiency than manifold injections, while lower emissions were observed in manifold injections [10]. Feroskhan et al studied the operation of a Homogeneous Charge Compression Ignition (HCCI) engine using simulated biogas and DEE as the primary and secondary fuels respectively.…”
Section: Introductionmentioning
confidence: 99%